2020
DOI: 10.1002/fsn3.1854
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and modeling of growth and lactic acid production in Gundruk, a Himalayan fermented vegetable dish

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…The change in correlation between acidification and growth under salt conditions suggests that these parameters may be independently affected in some cases. Our findings are consistent with previous studies that have shown that the production of lactic acid is only partially associated with growth (Alvarez et al, 2010;Ghimire et al, 2020). For strains with low growth but relatively high acidification, as is the case for Lactococcus lactis subsp.…”
Section: Discussionsupporting
confidence: 93%
“…The change in correlation between acidification and growth under salt conditions suggests that these parameters may be independently affected in some cases. Our findings are consistent with previous studies that have shown that the production of lactic acid is only partially associated with growth (Alvarez et al, 2010;Ghimire et al, 2020). For strains with low growth but relatively high acidification, as is the case for Lactococcus lactis subsp.…”
Section: Discussionsupporting
confidence: 93%
“…Kinetic models play an important role in monitoring and predicting fermentative processes involved in substrate utilization, growth, and product formation, and are recognized as an informative tool for rapid and cost-effective evaluation of microbial growth [9]. The doubling time is related to the growth specific rate, and both parameters can be used to describe changes in the number of microorganisms over time [48].…”
Section: Determination Of Growth Parametersmentioning
confidence: 99%
“…These models constitute a fundamental tool to determine the quantitative importance of bacteria, monitor and predict fermentative processes, and improve their analysis for biotechnological use. Likewise, they provide advanced information on the behavior of microorganisms using precise, repeatable, detailed experiments and mathematical models, which contribute to the design and control of biotechnological processes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to harness the potential of LAB acidification processes, it is critical to establish the effects of process parameters on the kinetics of the growth pattern of the bacteria. The key process parameters of essence include pH and harvesting time which directly impact the physiological state of the LAB after the fermentation process (Rault et al ., 2009; Ghimire et al ., 2020). An important fermentation process whereby starter cultures are essentially employed is in yoghurt production.…”
Section: Yoghurt Historymentioning
confidence: 99%